Resilience Psychoeducation for Adolescents in Orphanages - Karina, Annisa Dian; Suryaningrum, Cahyaning; Djudiyah (Edumedia Solution, 2026)
Orphanage adolescents face various developmental challenges that require strong adaptive skills. One skill that plays a crucial role in overcoming these difficulties is resilience. This community service activity aims to enhance adolescents’ knowledge and belief regarding resilience through psychoeducation focused on optimism and self-efficacy. The activity was conducted with nine adolescents at the AK Orphanage using methods such as lectures, group discussions, positive self-talk, case studies, and role-playing. Evaluation was carried out using a one-group pretest-posttest design with instruments measuring knowledge of resilience and belief in facing challenges. The results showed that the average knowledge score increased from 28.89 to 43.33, while the average belief score increased from 29.67 to 38.89. The results of the paired sample t-test indicated that the increases in both aspects were statistically significant (p < 0.001). These findings suggest that resilience psychoeducation can help improve adolescents’ knowledge and belief in facing various daily life challenge